KCa3.1 Promotes Proinflammatory Exosome Secretion by Activating AKT/Rab27a in Atrial Myocytes during Rapid Pacing - Dishiwen Liu; Huiyu Chen; Yuntao Fu; Yajun Yao; Shanqing He; Youcheng Wang; Zhen Cao; Xuewen Wang; Mei Yang; Qingyan Zhao (Cardiovascular Therapeutics)
Purpose. The aim of this study was to investigate the role of the medium-conductance calcium-activated potassium channel (KCNN4, KCa3.1) in the secretion of proinflammatory exosomes by atrial myocytes. Methods. Eighteen beagles were randomly divided into the sham group (n=6), pacing group (n=6), and pacing+TRAM-34 group (n=6). Electrophysiological data, such as the effective refractory period, atrial fibrillation (AF) induction, and AF duration, were collected by programmed stimulation. Atrial tissues were subjected to hematoxylin and eosin, Masson’s trichrome, and immunofluorescence staining. The expression of KCa3.1 and Rab27a was assessed by immunohistochemistry and western blotting. The downstream signaling pathways involved in KCa3.1 were examined by rapid pacing or overexpressing KCNN4 in HL-1 cells. Results. Atrial rapid pacing significantly induced electrical remodeling, inflammation, fibrosis, and exosome secretion in the canine atrium, while TRAM-34 (KCa3.1 blocker) inhibited these changes. Compared with those in control HL-1 cells, the levels of exosome markers and inflammatory factors were increased in pacing HL-1 cells. Furthermore, the levels of CD68 and iNOS in macrophages incubated with exosomes derived from HL-1 cells were higher in the pacing-exo group than in the control group. More importantly, KCa3.1 regulated exosome secretion through the AKT/Rab27a signaling pathway. Similarly, inhibiting the downstream signaling pathway of KCa3.1 significantly inhibited exosome secretion. Conclusions. KCa3.1 promotes proinflammatory exosome secretion through the AKT/Rab27a signaling pathway. Inhibiting the KCa3.1/AKT/Rab27a signaling pathway reduces myocardial tissue structural remodeling in AF.